In-hospital stroke in patients after cardiac surgery or invasive interventions - P. A. Filimonova; L. I. Volkova; A. M. Alasheev; A. V. Mikhaylov; E. A. Grichuk (Неврология, нейропсихиатрия, психосоматика, 2017)
Most in-hospital strokes occur after cardiac or vascular surgeries, during invasive therapeutic and diagnostic procedures on the heart and blood vessels. The incidence of stroke after coronary artery bypass grafting is about 2%; that after valve surgery and percutaneous cardiac intervention is 1 to 10% and 0.03 to 0.4%, respectively.Objective: to analyze the risk factors, pathogenetic, clinical, and laboratory characteristics of stroke after cardiac surgery and invasive interventions.Patients and methods. The investigation enrolled in-hospital stroke patients who had undergone invasive cardiac or open-heart surgery in Sverdlovsk Regional Hospital One in 2011 to 2015. A comparison group consisted of 196 patients with community-acquired stroke.Results. Stroke after cardiac surgical or endovascular interventions developed in 88 patients (44.9% of all the in-hospital stroke cases registered in the above period). The incidence of stroke after open-heart surgery was 0.97% (63 cases), depending on the type of surgery. Stroke following open-heart surgery was recorded after combined correction (1.4%), two-valve replacement surgery (1.98%), aortic and mammary coronary artery bypass grafting under extracorporeal circulation (1%), and beating heart bypass surgery (0.25%). The severity of stroke and the degree of disability did not differ in patients after invasive cardiac and open-heart surgeries.Conclusion. Patients who have undergone cardiac surgery and are at high risk for in-hospital stroke should be followed up and should receive preventive treatment for stroke in the early postoperative period.